UKRAINIAN MEDIALANDSCAPE IN THE TIME OF WAR (2022–2024): TRANSFORMATION, RESPONSE TO THE WAR, DYNAMICS OF MEDIA CONSUMPTION - Svitlana Bezchotnikova; Nina Zrazhevska (Інтегровані комунікації)
This article examines the impact of the Russian-Ukrainian hybrid war on the Ukrainian media landscape and media consumption. A mixed-method research methodology was used to reveal quantitative and qualitative changes. Despite losses in TV channels, radio stations and printed media, most media companies hadn't stopped broadcasting near war zone and launched united initiatives at the start of the war. Humanitarian media activities focused on crowdsourcing, fundraising, and information support for displaced people, army divisions, and the general Ukrainian public. The authors note that the peak of the humanitarian media campaigns for the war in Ukraine was during the first several months of the war. Most of the initiatives had long-term duration. The focus of crowdsourcing and fundraising campaigns, organized by the media, moved in dynamics primarily from people from the war zone who lost their work, home, and relatives in 2022-2023 towards army support and strengthening the defence of the country in 2023-2024. Increased news consumption through social networks was noted, with high trust in official sources like the President and Armed Forces. The media played a crucial role in national unity, with a strong emphasis on corporate social responsibility. Media consumption surveys identified disinformation narratives, strategies, and peculiarities of news consumption habits during the war.